2015
DOI: 10.3389/fnbeh.2015.00188
|View full text |Cite
|
Sign up to set email alerts
|

The framing effect and skin conductance responses

Abstract: Individuals often rely on simple heuristics when they face complex choice situations under uncertainty. Traditionally, it has been proposed that cognitive processes are the main driver to evaluate different choice options and to finally reach a decision. Growing evidence, however, highlights a strong interrelation between judgment and decision-making (JDM) on the one hand, and emotional processes on the other hand. This also seems to apply to judgmental heuristics, i.e., decision processes that are typically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…We verified that our experimental task was successful in eliciting risk-sensitive SCRs as suggested by the previous literature with this particular design (Ring, 2015;Ring et al, 2018;Ring & Kaernbach, 2015). To account for the dependencies among repeated data, we used random intercept models (package lme4 in R), which allow each participant to have a unique intercept (Bagiella et al, 2000).…”
Section: Influence Of Shock Probability On Scr Measuressupporting
confidence: 63%
See 1 more Smart Citation
“…We verified that our experimental task was successful in eliciting risk-sensitive SCRs as suggested by the previous literature with this particular design (Ring, 2015;Ring et al, 2018;Ring & Kaernbach, 2015). To account for the dependencies among repeated data, we used random intercept models (package lme4 in R), which allow each participant to have a unique intercept (Bagiella et al, 2000).…”
Section: Influence Of Shock Probability On Scr Measuressupporting
confidence: 63%
“…In previous studies, it was reported that this experimental design resulted in risksensitive SCRs during the anticipation phase, i.e., SCRs that correlated positively and significantly with the shock probability (Ring, 2015;Ring et al, 2018;Ring & Kaernbach, 2015).…”
Section: Methodsmentioning
confidence: 95%
“…Therefore, choosing to dedicate time and resources in the pursuit of “being scared” could create a positive bias toward achieving that goal (Habel, Alavi, Schmitz, Schneider, & Wieseke, 2016). Moreover, prepotent affect facilitated by agency and framing effects may further bias experienced affect (Fagley, Coleman, & Simon, 2010; Levin, Gaeth, Schreiber, & Lauriola, 2002; Ring, 2015). Voluntary engagement with negative information has also been shown to activate the same brain networks as engaging with positive information (Lindquist, Satpute, Wager, Weber, & Barrett, 2016).…”
mentioning
confidence: 99%
“…Emotions affect susceptibility to framing effects at a conscious ( Covey, 2014 ; Lecheler et al, 2015 ) and unconscious ( Ring, 2015 ) level. Furthermore, different frames engage different decision inputs within the brain.…”
Section: Discussionmentioning
confidence: 99%